Physical, psychological, and sexual violence on adolescents in junior high school, senior high school, and college - Aprianti; Anggraini, Fitria Dewi Puspita; Mubarokah, Kismi; Widya, Fhiqa Arisma (International Journal on Health and Medical Sciences, 2023)
Dating violence is the second highest cause after dating violence. Adolescents are a population at risk for dating violence. This study aimed to analyze the differences at each level of education for incidents of physical, psychological, and sexual violence in dating to provide specific interventions based on the educational level to prevent dating violence. This study used a cross-sectional design. The sample size was determined based on the calculation of the Slovin formula so that there were 267 samples for junior high school level, 304 for high school level, and 220 for College Level. The sample used had inclusion criteria including having dated and for respondents aged <17 years obtaining parental consent by filling out informed consent. Sampling was done using stratified random sampling. The technique of taking respondents at the junior and senior high school levels uses a list of classes with the same number of male and female students and uses the Google form. The data were tested for normality with the result that the data were not abnormally distributed with a significant value of 0.001, and the data were not homogeneous. Then a different test was carried out for three unpaired groups using the Kruskal-Wallis test. The results of the study showed that there were differences in the incidence of physical violence in courtship at the junior high school, high school, and college levels (p-value = 0.001), there were differences in the incidence of psychological violence in courtship at the junior high school, high school and university levels (p-value = 0.001), there were differences incidents of sexual violence in dating at the junior high school, high school and university levels (p-value = 0.001). It is necessary to provide education about preventing dating violence, especially for students, because dating violence is more common in universities